Edukasi Dini untuk Mencegah Penyimpangan Orientasi Seksual di SDN 2 Ciamis - Dina Oktaviani; Nana Mulyana; Elia Mahamanah; Salsabila Alawiyah; Ana Helistiana; Billy Hapid Ziaulhaq; Nurul Aulia (Yayasan Inspirasi El Burhani, 2022)
Introduction: The understanding of the children of SDN 2 Ciamis about sexual orientation deviations needs to be known and monitored. In today's era, children are generally attracted to the opposite sex. However, it is possible that children will have different sexual orientations. In this case, both parents are responsible for maintaining and guiding the child. The issue of sexual deviation has been the object of debate for quite a long time. After the emergence of a campaign carried out by the LGBT (lesbian, gay, bisexual and transgender) movement, this debate is increasingly visible. Objective: The purpose of this Community Service is to increase / increase knowledge from an early age to SDN 2 Ciamis students about sexual orientation deviations, and know what things should not be done to the opposite sex. Method: Before conducting Community Service, the team determines in advance the target that will be given Community Service. After selecting the target to be given Community Service, the team asked for permission from the school and made a time contract so that the activities could run without any obstacles. This activity was carried out at SDN 2 Ciamis. The method used in this activity is to tell the story of the Prophet Lut As followed by questions and answers. This activity lasts 45 minutes. The participants of the activity were grade 6 students at SDN 2 Ciamis. Result: The results of documented observations indicate an increase in the knowledge and insight of students at SDN 2 Ciamis. The pre-implementation evaluation showed that 7 out of 60 people responded to the questions given and could answer the questions correctly, but after community service, 30 out of 60 participants who gave feedback answered correctly and dared to come forward. Conclusion: Based on the evaluation results, community service activities to increase knowledge have been successful with individuals with indicators of timeliness and duration, participation, knowledge, and job descriptions. In the question and answer session/discussion, all participants enthusiastic to ask and answer and understand what is explained by the speaker. In the post-implementation evaluation session, participants answered what asked without hesitation. Results of observations showed an increase in participants' knowledge. The results of documented observations indicate an increase in the knowledge and insight of students at SDN 2 Ciamis. The pre-implementation evaluation showed that 7 out of 60 people responded to the questions and were able to answer the questions correctly, but after community service, 30 of the 60 participants who gave feedback answered correctly and dared to come forward to retell the story of the Prophet Lut. US This shows a change in the status of knowledge before and after the activity is carried out.